Use of active learning strategies in public affairs education: Advances and lessons from the scholarship and the practice. Issue 1 (March 2022) - Careaga-Tagüeña, Maite; Sanabria-Pulido, Pablo
Public affairs education can benefit from the potential of active learning practices in preparing students for the complex surroundings of real public service. This article aims to explore the use of those practices in public affairs education and the extent to which those practices are suitable in a public affairs school in a country in the global South. To do so, it follows a threefold analytical approach. First, from a sample of empirical works in public affairs, it explores the active learning practices portrayed in the literature of public affairs education and identifies patterns and practices. Then, through content analysis of syllabi from a sample of master level courses of schools of public affairs in the US and Europe it identifies the most frequent participant-centered learning practices used in public affairs education. Finally, by means of a case study from a public affairs school in Colombia, it analyzes the adoption of active learning practices to be effectively adopted in such setting and compares them with the two sets of practices previously analyzed. The analysis provided some insights. Both the literature review and the benchmark of practices in public affairs schools, reflect that public affairs education already relies on a wide array of active learning strategies, which, according to some empirical literature, appear to be highly useful in preparing students for public sector practice. Then, the analysis of the use of active learning practices in a Latin American school of public affairs revealed a similarly evident use such practices, something that appears to be instrumental for the faculty, students and alumni of the program, and whose implementation does not appear to differ from other programs abroad.